2020
DOI: 10.1021/acsami.0c15789
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching Memory Performance of Two-Dimensional Polyimide Covalent Organic Framework Films

Abstract: Two-dimensional polyimide covalent organic framework (2D PI-NT COF) films were constructed on indium-tin-oxide (ITO)-coated glass substrates to fabricate two-terminal sandwiched resistive memory devices. The 2D PI-NT COF films condensated from the reaction between 4,4',4''triaminotriphenylamine and naphthalene-1,4,5,8-tetracarboxylic dianhydride under solvothermal conditions demonstrated high crystallinity, good orientation preference, tunable thickness, and low surface roughness. The well-aligned electron don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 50 publications
1
82
0
Order By: Relevance
“…We think this is because the 2D framework of COF‐TT‐BT parallel to ITO substrate resulting in vertically aligned π columns, and thereby providing preassigned pathways so that electrons and holes can be transported through π‐cloud overlap [67] . Hence, the crystallinity contributes to facilitating the performance and stability of resistive switching memory devices, as also found by Liu and co‐workers [55] . As far as we know, COF‐TT‐BT is a state‐of‐the‐art 2D COF for nonvolatile memristors, and even one of the best resistive switching materials as compared with other novel 2D materials.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…We think this is because the 2D framework of COF‐TT‐BT parallel to ITO substrate resulting in vertically aligned π columns, and thereby providing preassigned pathways so that electrons and holes can be transported through π‐cloud overlap [67] . Hence, the crystallinity contributes to facilitating the performance and stability of resistive switching memory devices, as also found by Liu and co‐workers [55] . As far as we know, COF‐TT‐BT is a state‐of‐the‐art 2D COF for nonvolatile memristors, and even one of the best resistive switching materials as compared with other novel 2D materials.…”
Section: Resultsmentioning
confidence: 58%
“…prepared crystalline 2D porphyrinic COF films utilizing surfactant‐monolayer‐assisted interfacial synthesis strategy for a hybrid learning–erasing–forgetting memory as the pseudogate [54] . Subsequently, a write‐once–read‐many‐times (WORM) resistive switching memory device based on highly ordered 2D donor–acceptor (D‐A) COF film, PI‐NT , was reported by Liu and co‐workers [55] . The WORM memristor possessed bipolar current–voltage characteristics with a superior ON/OFF current ratio of 10 6 for positive voltage scan and 10 4 –10 6 for the negative scan, but a moderate retention time of 180 min.…”
Section: Introductionmentioning
confidence: 99%
“…The COF can also be used as an active material in memory devices [88]. By utilizing the charge accumulation at the interface between 2DBECOF-PP and SiO 2 , a FET-type memory device can be fabricated with typical hysteresis behavior during voltage sweeping, leading to a learning-erasing-forgetting memory process [89].…”
Section: Sensors Electrochromic Devices and Memory Devicesmentioning
confidence: 99%
“…COF-based materials have been developed for obtaining highly efficient organic semiconductors, such as FETs and photodetector devices. Moreover, the progress of thin-film processability and device integration has endowed COFs with extensive potential in resistive memory and memristor applications [47,108,109].…”
Section: Reviewsmentioning
confidence: 99%
“…More recently, Sun et al [108] reported a surface-grown donor-acceptor type 2D polyimide COF film (namely PI-NT COF), which was synthesized from the condensation between the electron-donating 4,4′,4″-triaminotriphenylamine and the electron-withdrawing naphthalene-1,4,5,8-tetracarboxylic dianhydride under solvothermal conditions. This 2D PI-NT COF film exhibited high crystallinity, good orientation preference, tunable thickness, and low surface roughness.…”
Section: Reviewsmentioning
confidence: 99%